Beach-seine net fishing : an analysis of the economic conditions and environment of the fishery in False Bay - James, I (Department of Biological Sciences, 2017)
This paper examines the economic effects of management policies on four of the seven beach-seine net fishing operations in False Bay. The effects of past regulations are examined by assessing whether or not this industry is at present profitable. It was found that under the present management policies all fishing crews are profitable. A new policy preventing fishermen from catching white steenbras has been introduced. This was examined and it was shown that only one of the crews examined would be effected. Two proposed policies were examined to determine their impact on the sector. The first proposal aims to remove kob as a target species, however none of the crews would be significantly effected by this proposal. The second proposal aims to restrict fishing to working days, this proposal would result in collapse of two crews. Long term feasibility was examined using three models that predict the NPV of income for each crew under different assumptions. It was shown that if stocks continue to decline and white steenbras remains restricted all crews except one would collapse. If stocks improve but the catching of white steenbras remains prohibited for IO years, one of the crews will collapse. The final section assessed the validity of a proposal that the Marine Resource Fund be used to buy trek fishermen's permits, it was concluded that this is not a feasible proposal.